2022
DOI: 10.3390/app12031245
|View full text |Cite
|
Sign up to set email alerts
|

Auger Electron Spectroscopy (AES) and X-ray Photoelectron Spectroscopy (XPS) Profiling of Self Assembled Monolayer (SAM) Patterns Based on Vapor Deposition Technique

Abstract: It is crucial to develop novel metrology techniques in the semiconductor fabrication process to accurately measure a film’s thickness in a few nanometers, as well as the material profile of the film. Highly uniform trichlorosilane (1H,1H,2H,2H-perfluorodecyltrichlorosilane, FDTS) derived SAM film patterns were fabricated by several conventional semiconductor fabrication methods combined, including photolithography, SAM vapor deposition, and the lift-off technique. Substantial information can be collected for F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…After exposure to the GCIB, decomposition of the alkane chain of the organic fragment and cleavage of the thiol–Au bond were observed at the earlier etching stage. Also, GICB sputtering was used to etch SAM patterns of trichlorosilane (1 H ,1 H ,2 H ,2 H -perfluorodecyltrichlorosilane, FDTS) on a silicon wafer for profiling and reconstructing the three-dimensional SAM patterns, 88 which demonstrated that FDTS SAM film patterns should be highly uniform. These results attested that the GCIB technique could be used as an efficient metrology for profiling film and layer-like materials.…”
Section: Gas Cluster Ion Beam Etchingmentioning
confidence: 99%
“…After exposure to the GCIB, decomposition of the alkane chain of the organic fragment and cleavage of the thiol–Au bond were observed at the earlier etching stage. Also, GICB sputtering was used to etch SAM patterns of trichlorosilane (1 H ,1 H ,2 H ,2 H -perfluorodecyltrichlorosilane, FDTS) on a silicon wafer for profiling and reconstructing the three-dimensional SAM patterns, 88 which demonstrated that FDTS SAM film patterns should be highly uniform. These results attested that the GCIB technique could be used as an efficient metrology for profiling film and layer-like materials.…”
Section: Gas Cluster Ion Beam Etchingmentioning
confidence: 99%
“…This technique is ideal as it gives information on the oxidation states and chemical environment of the studied species and allows estimation of the surface elemental composition once the relevant atomic sensitivity factors have been considered. [42][43][44][45][46] Figure 1C shows the highresolution XP spectrum of the functionalized carbon-BNQDs in C1s, B1s, N1s, and O1s energy region. In particular, in the C 1s binding energy region, the fitting of the spectrum required five Gaussian components centered at 285.0, 286.3, 288.0, 289.4, and 293.3 eV.…”
Section: Synthetic Strategy and Structure Of The Carbon-bnqdsmentioning
confidence: 99%
“…Surface characterization is not trivial and requires the use of several analytical methods with different characteristics. A summary of these characteristics for most common surface analysis techniques is listed in Table . These standard methods provide information only to a depth of some tens of nanometers. Since corrosive environmental conditions can lead to the development of several oxide layers of different morphologies and chemical nature on the sample surface in the case of CCAs with various layer thickness, deeper layers cannot be analyzed with abovementioned methods.…”
Section: Introductionmentioning
confidence: 99%